Improvement Gudang Finished Good di PT. FSCM Manufacturing Indonesia - Suyogo Jefton; Prayonne Adi (Jurnal Titra, 2016)
Existing problems at PT. FSCM Manufacturing Indonesia’s finished goods warehouse are the goods flow is not FIFO and insufficient capacity. Improvement will be conducted in both Plant II and Plant III PT. FSCM Manufacturing Indonesia. The current layout in both warehouse used block stacking method. The suggested design included change the storing method into pallet flow, change the layout, design a control board and work instruction. Pallet flow method will be applied by using roller conveyor. The design will make the goods flow FIFO and the PC Store can store all the goods.